Covenant and communion : the biblical theology of Pope Benedict XVI - Hahn, Scott (Grand Rapids, Mich. : Brazos Press, 2009)
Hahn argues that the heart of Benedict's theology is salvation history and the Bible and shows how Benedict accepts historical criticism but recognizes its limits. The author also explains how Benedict reads the overall narrative of Scripture and how he puts it to work in theology, liturgy, and Christian discipleship. --from publisher description
Ignorance of Scripture is ignorance of Christ : the theological project of Joseph Ratzinger -- The critique of criticism : beginning the search for a new theological synthesis -- The hermeneutic of faith : critical and historical foundations for a biblical theology -- The spiritual science of theology : its mission and method in the life of the church -- Reading God's testament to humankind : biblical realism, typology, and the inner unity of revelation -- The theology of the divine economy : covenant, kingdom, and the history of salvation -- The embrace of salvation : mystagogy and the transformation of sacrifice -- The cosmic liturgy : the Eucharistic kingdom and the world as temple -- The authority of mystery : the beauty and necessity of the theologian's task.
Includes bibliographical references and indexes.
Keywords: Benedict -- XVI, -- Pope, -- 1927-; Catholic Church -- Doctrines; Theology